The Influence of Work Culture, Competence and Work Environment on Employee Performance in Pariaman Tengah District, Pariaman City - Chayarlis, Chayarlis; Frinaldi, Aldri (Program Pascasarjana Universitas Negeri Makassar, 2021)
Without the support of adequate human resources, the activities of government agencies will not run well. How to manage human resources (HR) to become dynamic, productive hard workers to achieve Indonesia's Vision 2045.This research is to reveal the influence of work culture, competence and work environment of employees in District of Central Pariaman District, Pariaman CityThe research method used is associative quantitative method. The population in this study were 1 (one) district and 17 (seventeen) villages with 102 employees.The number of research samples was 81.3 rounded to 81 people. The sampling technique used in this research is Proportional Random Sampling.Data collection techniques used questionnaires and observation. Questionnaire testing was carried out with validity and reliability. Descriptive data analysis techniques used a percentage of the respondent's level of achievement and quantitative by using path analysis, before testing the hypothesis, first testing the analysis requirements with the normality test, linearity test and regression test.Based on the results of the analysis and discussion that has been done previously, it is concluded that (1) There is a direct effect of work culture on the work environment of employees of Central Pariaman District, Pariaman City by 28.4%. (2) There is a direct influence of competence on the work environment of employees of Central Pariaman District, Pariaman City, amounting to 13.8%. (3) There is a direct effect of work culture on employee performance in Central Pariaman District, Pariaman City by 28.2%. (4) There is a direct influence of competence on employee performance in Central Pariaman District, Pariaman City by 2.8%. (5) There is a direct effect of the working environment on the employee performance of the Central Pariaman District, Pariaman City of 9.2%.